The Influence of Patient Satisfaction and Trust on Revisit Intention Mediated by Word-of-Mouth Intention at Mom & Baby Clinic, Mangga Besar Branch - Mediana Sutopo Liedapraja; Hery Winoto Tj (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examined the impact of patient satisfaction and trust on revisit intention, mediated by word-of-mouth intention, at the Mom & Baby Clinic's Mangga Besar branch. The stagnation in the number of patient visits during 2023-2024, which only increased from 6,329 to 6,336 visits, far below the target of 8,000 visits, became the background of the study. With a quantitative approach, the study involved 130 respondents who were selected through purposive sampling. Hypothesis testing using the SEM-PLS method. The results showed that patient satisfaction and trust had a significant positive effect on both word-of-mouth intention and revisit intention. Patient trust had a more dominant influence (β=0.591) on word-of-mouth intention than satisfaction (β=0.249), while satisfaction had a stronger influence (β=0.291) on revisit intention than trust (β=0.240). Word of mouth intention effectively mediates the relationship between both patient satisfaction and trust with revisit intention. These findings highlight the importance of enhancing patient satisfaction and trust to encourage positive word of mouth and increase revisit intention.